A carbon-coated aluminum foil coating, and a preparation method and application thereof
Patent Information
- Application Number
- CN202511994886.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-12-26
AI Technical Summary
[0003]正常涂碳产品中,铝箔表面达因值要超过32dyn/mm,但由于生产工艺需要,铝箔厂家在生产过程中会使用不同的轧制油,使得铝箔表面沾染油污等污染物,导致铝箔表面达因值降低,使得下游工厂对铝箔进行加工时,铝箔表面达因值往往不超过30dyn/mm,这就导致实际生产过程中,下游工厂进行涂布时会出现涂碳层附着力差等问题
[0018]本发明有益效果:本发明制备的涂碳铝箔涂料由硫化处理的碳材料经改性粘结剂进行包裹,改性粘结剂中含有大量的金属盐基团,能够大幅提升涂料在铝箔表面的铺展能力,确保涂料能够均匀地覆盖铝箔表面,避免出现局部堆积或漏涂等问题;也强化了碳材料在粘结剂体系中的分散稳定性,有效防止碳材料在储存或工作过程中发生团聚,保障涂料成分的均匀性;同时,改性粘结剂中的非水解基团可与经硫化处理后的碳材料表面形成的极性基团形成牢固的相互作用,实现二者的精准锚定,确保碳材料能够被改性粘结剂均匀且紧密地包裹,形成稳定的核壳结构;即使使用的铝箔表面有油污,涂料中的异丙醇也可对油污进行溶解,而改性粘结剂中的水解基团则可与铝箔表面发生化学反应,形成稳定的化学键连接,碳材料和改性粘结剂的协同使得涂炭铝箔涂料与铝箔之间的附着力达到极高水平,即便针对表面达因值仅为24的铝箔,附着力也能达到400N,解决了低表面活性铝箔涂覆难题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of current collector technology, specifically relating to a carbon-coated aluminum foil coating, its preparation method, and its application. Background Technology
[0002] Carbon-coated aluminum foil is a composite material in which conductive paste is coated onto the surface of aluminum foil. As an important component of the positive electrode of lithium-ion batteries, it is widely used in electrochemical devices such as power batteries and energy storage batteries. Its performance directly affects the overall performance of the battery.
[0003] In normal carbon-coated products, the dyn value of the aluminum foil surface should exceed 32 dyn / mm. However, due to the needs of the production process, aluminum foil manufacturers use different rolling oils during production, which causes the aluminum foil surface to be contaminated with oil and other pollutants, resulting in a decrease in the dyn value of the aluminum foil surface. As a result, when downstream factories process the aluminum foil, the dyn value of the aluminum foil surface often does not exceed 30 dyn / mm. This leads to problems such as poor adhesion of the carbon coating layer when downstream factories apply the coating during actual production.
[0004] In related technologies, downstream factories usually need to further process aluminum foil, such as corona treatment and chemical cleaning, to improve its surface dyne value, which involves complex processes and is time-consuming and labor-intensive.
[0005] In summary, to overcome the negative impact of aluminum foil variations on its performance, this invention provides a carbon-coated aluminum foil coating, its preparation method, and its application. Summary of the Invention
[0006] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0007] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a carbon-coated aluminum foil coating, its preparation method, and its application.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a carbon-coated aluminum foil coating, prepared from the following components in the following mass percentages: Carbon materials 4.8%~7.2%; modified binder 40%~60%; balance is conductive solvent; The modified adhesive uses a water-soluble acrylic resin copolymerized with maleic anhydride as the matrix. The pH value of the matrix is adjusted sequentially by a metal alkali and an organic alkali. Organometallic salt groups are introduced through the neutralization and modification of metal ions in the metal alkali. 1g of the modified adhesive contains 1.92 to 7.6 mmol of the organometallic salt groups.
[0009] Furthermore, the mass ratio of the carbon material to the modified binder is 1:5~8.
[0010] Furthermore, the carbon material is at least one of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0011] Furthermore, the organometal salt groups include metal carboxylates and metal sulfonates.
[0012] Furthermore, the carbon material undergoes a sulfidation treatment.
[0013] Furthermore, the conductive solvent is a mixture of isopropanol and deionized water in a mass ratio of 1:3.
[0014] Furthermore, the metal alkali includes sodium hydroxide.
[0015] Furthermore, the organic base includes ammonia.
[0016] This invention also provides a method for preparing a carbon-coated aluminum foil coating, comprising the following steps: S1: Add the modified binder to the conductive solvent and mix to obtain a mixed slurry; S2: Add carbon materials to the mixed slurry, mix, and then grind and filter to obtain carbon-coated aluminum foil coating.
[0017] The present invention also provides a carbon-coated aluminum foil, comprising an aluminum foil substrate and a conductive coating, characterized in that: the conductive coating is obtained by coating the carbon-coated aluminum foil coating prepared by the preparation method onto the surface of the aluminum foil substrate and then curing it.
[0018] The beneficial effects of this invention are as follows: The carbon-coated aluminum foil coating prepared by this invention consists of sulfurized carbon material coated with a modified binder. The modified binder contains a large number of metal salt groups, which can significantly improve the coating's spreading ability on the aluminum foil surface, ensuring that the coating can uniformly cover the aluminum foil surface and avoiding problems such as local accumulation or missed coating. It also enhances the dispersion stability of the carbon material in the binder system, effectively preventing the carbon material from agglomerating during storage or operation, and ensuring the uniformity of the coating composition. At the same time, the non-hydrolyzable groups in the modified binder can react with the polar groups formed on the surface of the sulfurized carbon material. A strong interaction is formed, achieving precise anchoring between the two and ensuring that the carbon material can be uniformly and tightly wrapped by the modified binder to form a stable core-shell structure. Even if the aluminum foil surface is oily, the isopropanol in the coating can dissolve the oil, while the hydrolyzable groups in the modified binder can react chemically with the aluminum foil surface to form stable chemical bonds. The synergy between the carbon material and the modified binder enables the adhesion between the carbon-coated aluminum foil coating and the aluminum foil to reach an extremely high level. Even for aluminum foil with a surface dyne value of only 24, the adhesion can reach 400N, solving the problem of coating low surface activity aluminum foil.
[0019] This invention, thanks to the excellent adhesion properties of its special coating system, achieves a breakthrough by enabling direct coating of aluminum foil without any pretreatment. This eliminates the pretreatment step in the production process, significantly simplifying the preparation process of carbon-coated aluminum foil, reducing equipment investment and maintenance costs, and minimizing the consumption of chemical reagents and the generation of related waste during pretreatment. It is both economical and environmentally friendly. At the same time, the simplification of the process significantly shortens the production cycle and greatly improves production efficiency, laying a technological foundation for the large-scale promotion of carbon-coated aluminum foil.
[0020] In this invention, the amount and composition of the binder are optimized to avoid forming an insulating layer that hinders conductive pathways. Simultaneously, the sulfidated carbon material retains excellent conductivity, and its uniformly dispersed structure enables the construction of a continuous and stable conductive network. Therefore, the carbon-coated aluminum foil coating of this invention possesses excellent dispersion properties and ensures coating quality without adversely affecting the conductivity of the positive electrode. This effectively improves the overall performance of end products, such as batteries, and broadens the application range of carbon-coated aluminum foil.
[0021] This invention, through innovative material formulation design, not only solves the key technical pain points in the existing production of carbon-coated aluminum foil, such as insufficient adhesion, complex processes, high costs, and contradictory performance, but also achieves synergistic optimization of coating performance, production efficiency, and end-application effects, possessing extremely high technical value and market application prospects. Detailed Implementation
[0022] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0023] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0024] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0025] In this invention, the adhesive used was purchased from Sichuan Indile Materials Technology Group Co., Ltd., and the model number is 137D5.
[0026] Copolymer modification of the binder using maleic anhydride includes the following steps: S1: Add the binder and deionized water to the reactor, heat to 65-75℃ and stir to dissolve, then add the initiator, add maleic anhydride dropwise, and keep warm to copolymerize for 2-3 hours to obtain maleic anhydride modified acrylic resin prepolymer. S2: Cool the maleic anhydride-modified acrylic resin prepolymer to 45-55℃, add sodium hydroxide solution dropwise, adjust the pH value to 6.0-7.5, keep it at this temperature for 1-1.5 hours, then add ammonia water and adjust the pH value to 7.5-9.0 to obtain a water-soluble modified adhesive.
[0027] The carbon material was purchased from Shanghai Guangshu New Materials Co., Ltd., model number 70VP.
[0028] The high-temperature gas-phase sulfidation method is used to sulfide carbon materials, including the following steps: S1: The carbon material is vacuum dried at 120℃ for 4 hours to remove moisture and impurities, resulting in dried carbon material. S2: Place the dried carbon material and sulfur powder at a mass ratio of 1:0.8 at both ends of a tube furnace, purge with nitrogen, heat to 600-800℃, hold for 2-4 hours, and then cool naturally to room temperature. Wash with carbon disulfide to remove free sulfur, and vacuum dry at 80℃ for 8 hours to obtain carbon sulfide material.
[0029] Example 1 This embodiment provides a method for preparing carbon-coated aluminum foil, including the following steps: 1) Add 40 kg of the modified binder to 52.8 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 7.2 kg of carbon sulfide material to the mixed slurry and disperse it evenly. After grinding and sieving, carbon-coated aluminum foil coating is obtained. 3) The carbon-coated aluminum foil coating is applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90°C, a conductive coating with a thickness of 3 μm is formed, thus obtaining the carbon-coated aluminum foil of this embodiment.
[0030] Example 2 This embodiment provides a method for preparing carbon-coated aluminum foil, including the following steps: 1) Add 45 kg of the modified binder to 48.7 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 6.3 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) The carbon-coated aluminum foil coating is applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90°C, a conductive coating with a thickness of 3 μm is formed, thus obtaining the carbon-coated aluminum foil of this embodiment.
[0031] Example 3 This embodiment provides a method for preparing carbon-coated aluminum foil, including the following steps: 1) Add 50 kg of the modified binder to 43 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 7 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) The carbon-coated aluminum foil coating is applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90°C, a conductive coating with a thickness of 3 μm is formed, thus obtaining the carbon-coated aluminum foil of this embodiment.
[0032] Example 4 This embodiment provides a method for preparing carbon-coated aluminum foil, including the following steps: 1) Add 55 kg of the modified binder to 37.6 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 7.4 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) The carbon-coated aluminum foil coating is applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90°C, a conductive coating with a thickness of 3 μm is formed, thus obtaining the carbon-coated aluminum foil of this embodiment.
[0033] Example 5 This embodiment provides a method for preparing carbon-coated aluminum foil, including the following steps: 1) Add 60 kg of the modified binder to 40 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 10 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) The carbon-coated aluminum foil coating is applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90°C, a conductive coating with a thickness of 3 μm is formed, thus obtaining the carbon-coated aluminum foil of this embodiment.
[0034] Comparative Example 1 Comparative Example 1, based on Example 1, provides a method for preparing carbon-coated aluminum foil, comprising the following steps: 1) Add 40 kg of the modified binder to 52.8 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 8.2 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) Carbon-coated aluminum foil coating was applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90℃, a conductive coating with a thickness of 3 μm was formed, resulting in the carbon-coated aluminum foil of Comparative Example 1.
[0035] Comparative Example 2 Comparative Example 2, based on Example 1, provides a method for preparing carbon-coated aluminum foil, comprising the following steps: 1) Add 60 kg of the modified binder to 33.7 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 6.3 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) Carbon-coated aluminum foil coating was applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90℃, a conductive coating with a thickness of 3 μm was formed, resulting in the carbon-coated aluminum foil of Comparative Example 2.
[0036] Comparative Example 3 Comparative Example 3, based on Example 1, provides a method for preparing carbon-coated aluminum foil, comprising the following steps: 1) Add 40 kg of modified binder to 52.8 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 1.5 mmol of organometallic sodium salt group) to obtain a mixed slurry; 2) Add 7.2 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) Carbon-coated aluminum foil coating was applied to both sides of an aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm. After drying and curing at 90℃, a conductive coating with a thickness of 3 μm was formed, resulting in the carbon-coated aluminum foil of Comparative Example 3.
[0037] Comparative Example 4 Comparative Example 4, based on Example 1, provides a method for preparing carbon-coated aluminum foil, comprising the following steps: 1) Add 45 kg of the modified binder to 48.7 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 1.5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 6.3 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) Aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm was subjected to corona treatment (8KW). Then, carbon-coated aluminum foil coating was applied to both sides of the corona-treated aluminum foil substrate and dried and cured at 90℃ to form a conductive coating with a thickness of 3 μm, thus obtaining the carbon-coated aluminum foil of Comparative Example 4.
[0038] Comparative Example 5 Comparative Example 5, based on Example 1, provides a method for preparing carbon-coated aluminum foil, comprising the following steps: 1) Add 50 kg of the modified binder to 43 kg of conductive solvent and disperse and mix (1 gram of the modified binder contains 1.5 mmol of organometallic sodium salt groups) to obtain a mixed slurry; 2) Add 7 kg of carbon material to the mixed slurry and disperse it evenly. After grinding and sieving, the carbon-coated aluminum foil coating is obtained. 3) Aluminum foil substrate with a surface dyn value of 24 dyn / mm and a thickness of 13 μm was subjected to corona treatment (8KW). Then, carbon-coated aluminum foil coating was applied to both sides of the corona-treated aluminum foil substrate and dried and cured at 90℃ to form a conductive coating with a thickness of 3 μm, thus obtaining the carbon-coated aluminum foil of Comparative Example 5.
[0039] The coating adhesion, incomplete coating rate, and conductivity of the carbon-coated aluminum foils prepared in the examples and comparative examples were tested respectively. The test results are shown in Table 1. The specific test standards and procedures are as follows: Adhesion test: tensile testing machine, model C610, tensile speed 50mm / min, effective length 50mm, sample width 12.7mm, ineffective head length 10mm, ineffective tail length 10mm.
[0040] Conductivity: A four-probe resistance tester (Magic3R) was used to test the pressure at 25MPa, the holding time at 15s, the pressure increase rate at 1MPa / s, and the pressure decrease rate at 5MPa / s.
[0041] Number of missed coating points: Randomly select 50m~100m samples and use CCD to detect the missed coating points.
[0042] Table 1
[0043] As shown in Table 1, the carbon-coated aluminum foil coating prepared by this invention can still achieve an adhesion of over 400N even when the aluminum foil dyne value is only 24. This is because the hydrolytic groups of the modified binder form chemical bonds with the aluminum foil surface, and the non-hydrolytic groups of the modified binder anchor the polar groups on the carbon material surface, enabling it to disperse evenly and thus improving the adhesion of the coating. Furthermore, the coating adhesion increases with the increase of the amount of modified binder, without affecting the conductivity of the carbon-coated aluminum foil. The number of missed coating points can meet the normal production testing standards.
[0044] In Comparative Example 1, the amount of modified binder used was insufficient, failing to achieve complete and uniform encapsulation of the carbon material. Some carbon material particles were exposed due to ineffective encapsulation, leading to localized agglomeration in the coating system. This resulted in uneven particle accumulation on the coating surface, preventing continuous and tight contact with the aluminum foil surface. Secondly, insufficient modified binder directly resulted in an insufficient number of effective groups for bonding with the aluminum foil surface, failing to meet the requirements for large-area bonding. Only a small number of chemical bonds could be formed locally on the aluminum foil, with most of the coating and aluminum foil only undergoing physical adsorption, resulting in extremely weak adhesion. At the same time, the insufficient modified binder could not effectively connect the carbon material and aluminum foil, further weakening the interfacial bonding between the carbon material and aluminum foil. Ultimately, this led to extremely poor coating adhesion, making it prone to peeling and flaking.
[0045] In Comparative Example 2, excessive modified binder forms an overly thick coating layer on the carbon material surface. Unreacted modified binder molecules form an inert layer inside the coating, which not only increases the internal stress of the coating but also causes cracks due to uneven shrinkage during the drying process. At the same time, excessive modified binder leads to an excessively high concentration of sodium salt groups in the coating system, resulting in an abnormally low surface tension and "sagging" during coating, which disrupts the uniformity of the coating. Excessive hydrolytic groups can also undergo excessive condensation reactions on the aluminum foil surface, which can break under slight external disturbances, thus reducing the adhesion of the coating.
[0046] The modified binder used in Comparative Example 3 has fewer sodium salt groups in its molecular structure, which makes it impossible to form a strong anchoring bond with the polar groups on the surface of the sulfurized carbon material. This causes the carbon material to easily agglomerate in the coating system, resulting in poor uniformity of the coating after coating, and even a large number of pores and defects. Especially for low surface energy aluminum foil, conventional binders have poor spreadability and are difficult to form a continuous coating on the aluminum foil surface, ultimately resulting in low coating adhesion and failing to meet the requirements of practical applications.
[0047] Although Comparative Examples 4 and 5 also used modified adhesives with fewer sodium salt groups, the aluminum foil surface was modified through corona treatment. Corona treatment uses high-energy particles to bombard the aluminum foil surface, breaking some of its surface chemical bonds and forming a large number of polar active groups such as hydroxyl and carboxyl groups. At the same time, it increases the surface roughness of the aluminum foil, increases its contact area with the coating, and enhances the interaction force between the aluminum foil and the conventional adhesive to a certain extent, improving the spreading and adhesion of the adhesive on the aluminum foil surface. The increase in surface roughness can produce a mechanical interlocking effect, further assisting in enhancing the bonding force between the coating and the aluminum foil. Therefore, its adhesion is improved compared to Comparative Example 3, which uses untreated aluminum foil with a conventional adhesive. Even so, it still cannot achieve the high adhesion of 415N in this application because the molecular structure of the adhesive is not optimized, and the bonding defects between it and the carbon material have not been improved. In addition, conventional adhesives and aluminum foil mainly rely on physical action and mechanical interlocking to achieve adhesion, and their upper limit of adhesion is low. The surface activity improvement of aluminum foil brought about by corona treatment can only alleviate the adhesion problem to a certain extent, but cannot fundamentally solve the core problem of insufficient adhesive function. Therefore, its adhesion improvement is limited and far from the technical level of this application. Moreover, corona treatment will add additional production steps, equipment investment and energy consumption, resulting in complicated production process and increased cost.
[0048] In this application, through innovative material formulation design and precise control of binder dosage and structure, the adhesion between the carbon coating and the aluminum foil surface is significantly improved, reaching up to 415N. This helps to improve the conductivity of lithium batteries and extend their service life, meeting market demands. It overcomes key technical pain points in the existing production of carbon-coated aluminum foil, such as complex processes, high costs, and performance contradictions, and achieves synergistic optimization of coating performance, production efficiency, and end-application effects. It has extremely high technical value and market application prospects.
[0049] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A carbon-coated aluminum foil coating, characterized in that, It is prepared from the following components in the following mass percentages: Carbon materials: 4.8%~7.2%; Modified adhesive 40%~60%; the balance is conductive solvent; The modified binder uses a water-soluble acrylic resin copolymerized with maleic anhydride as the matrix. The pH of the matrix is adjusted sequentially by a metal alkali and an organic alkali. Organometallic salt groups are introduced through the neutralization and modification of metal ions in the metal alkali. 1g of the modified binder contains 5-7.6mmol of the organometallic salt groups. The mass ratio of the carbon material to the modified binder is 1:5-8. The conductive solvent is a mixture of isopropanol and deionized water in a mass ratio of 1:
3. The carbon material is vulcanized using a high-temperature gas-phase vulcanization method. Copolymer modification of the binder using maleic anhydride includes the following steps: S1: Add the binder and deionized water to the reactor, heat to 65-75℃ and stir to dissolve, then add the initiator, add maleic anhydride dropwise, and keep warm to copolymerize for 2-3 hours to obtain maleic anhydride modified acrylic resin prepolymer. S2: Cool the maleic anhydride-modified acrylic resin prepolymer to 45-55℃, add sodium hydroxide solution dropwise, adjust the pH value to 6.0-7.5, keep it at this temperature for 1-1.5 hours, then add ammonia water and adjust the pH value to 7.5-9.0 to obtain a water-soluble modified adhesive.
2. The carbon-coated aluminum foil coating as described in claim 1, characterized in that: The carbon material is at least one of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
3. The method for preparing carbon-coated aluminum foil as described in any one of claims 1 to 2, characterized in that, Includes the following steps: S1: Add the modified binder to the conductive solvent and mix to obtain a mixed slurry; S2: Add carbon materials to the mixed slurry, mix, and then grind and filter to obtain carbon-coated aluminum foil coating.
4. A carbon-coated aluminum foil, comprising an aluminum foil substrate and a conductive coating, characterized in that: The conductive coating is obtained by coating the surface of the aluminum foil substrate with the carbon-coated aluminum foil coating prepared by the preparation method described in claim 3 and then curing it.
Citation Information
Patent Citations
Anode water-based carbon-coated aluminum foil coating and preparation method thereof
CN115241424A
Radiation-hardened coatings with improved adhesive strength
WO2003060029A2
